The Ihya' As-Sunnah Movement Of Rice By Lazismu At The Darul Arqom Mosque, Batu Rinngit Kel. Karang Pule, Mataram, NTBArticle Sidebar - Susilo Sudarman (International Journal of Sociology of Religion, 2023)
This article will discuss the ihya' as-sunnah movement for rice by lazismu at the darul arqom mosque, batu ringgit kel. karang pule, mataram, NTB. This study aims to see how Lazismu performs in an effort to revive the sunnah (Living Qur`an-Hadith) through the distribution of shadaqah lunches for Friday prayers in congregation at the Darul-Arqam Batu Ringgit mosque, Karang Pule sub-district. Even beyond that, Lazismu has also indirectly preached Islamic teachings in the form of hadiths of Rasulullah SAW which are very rarely known by the local community. Looking at the results of the research above, the author can describe the pattern of interaction of Living Qur'an-Hadith with traditions built by Lazismu through its program is the puritanism-based Living Qur'an-Hadith model, namely a pure understanding of the text which is lived in the form of tradition once a week. When depicted in the form of a Venn diagram, the diagram patterns are not separate from one another, nor are they intersected, but all parts of one set are part of another set.